ANALISIS PENGUJIAN KAPASITAS BATERAI 220 VDC UNTUK KEANDALAN PLTGU UNIT PEMBANGKITAN (UP) BELAWAN - Wahyu Desmandra; Dino Erivianto; Rahmaniar (CV. Hawari, 2025)
This study aims to analyze the capacity of a 220 VDC battery used in the acoustic system of the Gas and Steam Power Plant (PLTGU) at the Belawan Generating Unit (UP). Batteries have an important role as a backup energy source in maintaining the continuity of the electrical operational system, especially in emergency conditions. The research method includes testing the battery capacity by measuring current, voltage, and discharge time under various load conditions. The test results show that battery capacity can vary depending on temperature, age, and previous charging conditions. The data obtained are explained to rotate the battery performance in supporting the PLTGU system. This conclusion provides recommendations for routine maintenance and battery replacement, to ensure the electrical system at the Belawan UP continues to function optimally. This research is expected to be a reference for PLTGU managers in improving the efficiency of the power plant system.